Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd001878.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Non-invasive physical treatments for chronic/recurrent headache

Abstract: Background Non-invasive physical treatments are often used to treat common types of chronic/recurrent headache. Objectives To quantify and compare the magnitude of short-and long-term effects of non-invasive physical treatments for chronic/recurrent headaches. Search strategy We searched the following databases from their inception to November 2002: MEDLINE, EMBASE, BIOSIS, CINAHL, Science Citation Index, Dissertation Abstracts, CENTRAL, and the Specialised Register of the Cochrane Pain, Palliative Care and Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 60 publications
3
103
0
4
Order By: Relevance
“…17 Studies examining the role of the cervical spine to headache (ie, "cervicogenic headache") have been well described in the literature. [18][19][20][21][22][23][24][25][26][27][28][29][30] However, the relation of the cervical spine to migraine is less well documented. [10][11][12][13][14][15] Previous studies by this author have demonstrated an apparent reduction in migraines after CSMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Studies examining the role of the cervical spine to headache (ie, "cervicogenic headache") have been well described in the literature. [18][19][20][21][22][23][24][25][26][27][28][29][30] However, the relation of the cervical spine to migraine is less well documented. [10][11][12][13][14][15] Previous studies by this author have demonstrated an apparent reduction in migraines after CSMT.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] This is especially important in comparison of migraine patients who may be suitable for chiropractic manipulative therapy. [23][24][25][26][27][28] Between 40% and 66% of patients with migraine, particularly those with severe or frequent migraine attacks, do not seek help from a physician. 29 Among those who do, many do not continue regular physician visits.…”
Section: Discussionmentioning
confidence: 99%
“…It has some significant effect with focal, segmental chronic pain, however the results in widespread pain are equivocal. [13,40,[69][70][71][72][73] …”
Section: Manual Therapymentioning
confidence: 99%
“…The results of one study [31] included in the Cochrane review on noninvasive treatments for headache pain [32] led the review authors to conclude that moderate evidence shows that TT is superior to placebo TT for reduction of tension-type headache pain within a few hours of a single treatment. Other published controlled trials have revealed greater reductions in pain for TT, relative to mock TT, for knee OA [33] and mixed chronic musculoskeletal problems [34].…”
Section: Therapeutic Touch/healing Touchmentioning
confidence: 99%
“…One should note, however, that in some cases, such as acupuncture, these conclusions are based on only one RCT. The Cochrane Collaboration also reviewed noninvasive physical treatments for chronic/recurrent headache [32] but only one trial (reported in two studies [57][58]) examined massage. This trial found SMT to be superior to massage for cervicogenic headache [57][58], whereas another trial not included in the Cochrane review found greater pain reduction for massage relative to acupuncture in patients with migraine but not tensiontype or combined headaches [59].…”
Section: Massage Therapymentioning
confidence: 99%